GE_GERICHTE P/20528/2022 vom 31. Juli 2023 - GE Cour de justice (2023)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;FAUX DANS LES CERTIFICATS;PERMIS DE CONDUIRE;CONFISCATION(DROIT PÉNAL) | CPP.310; CP.252; CP.69